Does fiscal decentralization help Indonesia avoid the middle-income trap? - Darius Tirtosuharto (Asian Development Bank Institute (ADBI), 2017)
This paper focuses on the impact of fiscal decentralization on the efficiency of fiscal resources at the regional level that will improve the probability of Indonesia avoiding the middle-income trap. From a development standpoint, the implementation of decentralization is not only aimed at increasing fiscal capacity and efficiency, but also at enhancing institutional quality at the local level to support economic growth. A nonparametric method of data envelopment analysis (DEA) is utilized to measure the fiscal efficiency scores of state governments. In the second stage of empirical analysis, a Tobit panel model is constructed to find key factors that affect state fiscal efficiency in Indonesia. The finding of this study confirms that the degree of fiscal decentralization is the key determinant of state fiscal efficiency. Hence, despite the positive impact of fiscal decentralization in Indonesia, the expansion of the state's fiscal spending has caused some degree of inefficiency due to a growing corruption and rent seeking. This could jeopardize the speed and extent of development in the Indonesian regions and also the transition into high-income countries.
Keywords: H30; H72; R50; 330; fiscal decentralization; institutional development; public expenditure